Livestock researchers announce the eradication of rinderpest - International Livestock Research Institute (International Livestock Research Institute, 2010)
John McDermott, the deputy director general for research at the International Livestock Research Institute (ILRI), talks about what the eradication of rinderpest means for livestock farmers around the world in a BBC World Service interview held on 15 October 2010.